Cyber Security and Privacy Trust in the Digital World and Cyber Security and Privacy EU Forum 2013, Brussels, Belgium, April 2013, Revised Selected Papers - Felici, Massimo.; Felici, Massimo. (Communications in Computer and Information Science,, 2013)
The CCIS series is devoted to the publication of peer-reviewed proceedings of conferences and workshops. Its aim is to efficiently disseminate original research results in computer science. All CCIS proceedings are available in electronic form from the SpringerLink digital library, and as printed books, and reach libraries and readers worldwide via Springer’s distribution network. Besides globally relevant meetings with internationally representative program committees guaranteeing a strict peer-reviewing and paper-selection process, conferences run by societies or of high regional or national relevance are also considered for publication. Application-oriented and interdisciplinary conferences are also welcome. The topical scope of CCIS spans the entire spectrum of computer science ranging from foundational topics in the theory of computing to information and communications science and technology and a broad variety of interdisciplinary application fields. CCIS proceedings can be published in time for distribution at conferences or as revised proceedings after the event. The publication is free of charge and an Open Access option is available at a fee. The language of publication is exclusively English. CCIS is abstracted/indexed in DBLP, Google Scholar, EI-Compendex, Mathematical Reviews, SCImago, and Scopus. CCIS volumes are also submitted for inclusion in ISI Proceedings. To start the evaluation of your proposal for inclusion in the CCIS series, please send an e-mail to ccis@springer.com. Detailed information on CCIS can be found at http://www.springer.com/series/7899.